Circles of Support and Self-Direction: An Interview Highlighting a Journey of Friendship and Managing Services. Issue 2 (May 2022) - Lockman Turner, Elissa; Bubash, Sarah; Fialka-Feldman, Micah; Hayes, Andrea
All people need different supports to be successful in their daily lives. For individuals with intellectual disabilities, support needs have traditionally been agency-directed. Circles of Support shift the control over who identifies and directs those support needs from an agency-directed model to a self-directed model, putting the individual with an intellectual disability at the center of a self-selected team of individuals involved across all environments in their daily life. By reconceptualizing how individuals identify and receive supports, individuals are given the control and agency needed to live a self-determined life. This interview is with two people working together in a different way from traditional agency-directed supports, shifting control over decisions from the provider agency to the person with a disability, allowing for greater control over all areas of his life.